Aplicativo Para Cotizaciónes De Fletes Internacionales En Fresenius Medical Care Andina S.A.S. (2022)
The business practice was developed in the company Fresenius Medical Care, which is located in the Intexzona Permanent Free Trade Zone, specifically in Cota, department of Cundinamarca. It is important to mention that Fresenius Medical Care, which from now on will be called FMC, is a company dedicated to global health care. Its main activities are focused on the research, design, development, engineering and manufacturing of products for medical treatment and the provision of preventive and hospital health services.